2010
DOI: 10.1109/tsmcb.2009.2032363
|View full text |Cite
|
Sign up to set email alerts
|

Random Early Detection for Congestion Avoidance in Wired Networks: A Discretized Pursuit Learning-Automata-Like Solution

Abstract: Abstract-In this paper, we present a learning-automata-like 1 (LAL) mechanism for congestion avoidance in wired networks. Our algorithm, named as LAL Random Early Detection (LALRED), is founded on the principles of the operations of existing RED congestion-avoidance mechanisms, augmented with a LAL philosophy. The primary objective of LALRED is to optimize the value of the average size of the queue used for congestion avoidance and to consequently reduce the total loss of packets at the queue. We attempt to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Convergence to fairness has been a topic that attracted significant attention from the networking research community, for several network types ranging from the internet in general (Tan and Yang, 2009;Misra et al, 2010) to machine-to-machine (Ferdouse et al, 2015;Teja et al, 2015), healthcare (Misra et al, 2009b;Misra and Chatterjee, 2014) and wireless networks (Dhurandhe et al, 2011;Chatterjee and Misra, 2014;Dhurandher et al, 2009;Yadav et al, 2014). The focus of the present study is the fair allocation of bandwidth to internet TCP flows.…”
Section: Related Workmentioning
confidence: 99%
“…Convergence to fairness has been a topic that attracted significant attention from the networking research community, for several network types ranging from the internet in general (Tan and Yang, 2009;Misra et al, 2010) to machine-to-machine (Ferdouse et al, 2015;Teja et al, 2015), healthcare (Misra et al, 2009b;Misra and Chatterjee, 2014) and wireless networks (Dhurandhe et al, 2011;Chatterjee and Misra, 2014;Dhurandher et al, 2009;Yadav et al, 2014). The focus of the present study is the fair allocation of bandwidth to internet TCP flows.…”
Section: Related Workmentioning
confidence: 99%
“…The authors have compared their work with respect to voice and data traffic and showed that it can control congestion based on the available delay information. Misra et al [20] has presented a unique technique based on automata theory for managing the congestion over wired network. The author have also applied stochastic-learning based mechanism and cellular automata for managing an effective queue size.…”
Section: Related Workmentioning
confidence: 99%
“…There is a large number of research works related to the subject. For example, [5][6][7] focused on the parameter settings to improve the service performance. In order to enhance the robustness of RED, researchers developed some algorithms based on RED such as Adaptive RED [8], Blue [9], and Weighted RED [10].…”
Section: Related Workmentioning
confidence: 99%